2018
DOI: 10.1177/1751143718767060
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of invasive mechanical ventilation in patients with severe blunt chest trauma and lung contusion: A French multicentric evaluation of practices

Abstract: Introduction: This study investigated invasive mechanical ventilation modalities used in severe blunt chest trauma patients with pulmonary contusion. Occurrence, risk factors, and outcomes of early onset acute respiratory distress syndrome were also evaluated. Methods: We performed a retrospective multicenter observational study including 115 adult patients hospitalized in six level 1 trauma intensive care units between April and September of 2014. Independent predictors of early onset acute respiratory distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Patients with PC had longer periods receiving assisted ventilation, ICU stays and total length of hospital stays. These findings were consistent with those of a previous study ( 4 ). However, there was no difference in mortality between the PC group and the non-PC group.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Patients with PC had longer periods receiving assisted ventilation, ICU stays and total length of hospital stays. These findings were consistent with those of a previous study ( 4 ). However, there was no difference in mortality between the PC group and the non-PC group.…”
Section: Discussionsupporting
confidence: 94%
“…Several studies have shown that PC patients have high incidences of negative pulmonary outcomes ( 4 , 22 ). The present study showed that patients with PC were more likely to develop ARDS, were more likely to be admitted to the ICU and receive mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, over 85% of our patients had pulmonary coinjuries, which according to recent publications are linked to the need for ventilatory support. 21,22 Epidural analgesia was administered in 1.6% and SSRF was performed in 4.0% of our patients; therefore, we think, it had limited effect on outcomes. Epidural analgesia was rarely used in our institutions, which can be explained by patient sedation and intubation before or within the first few hours of admission, restricted use of epidurals to 5 d due to infectious risks, contraindications to use in patients who receive anticoagulation as venous thromboembolism prophylaxis, and severity of injury.…”
Section: Variablementioning
confidence: 86%
“…A recent French observational study (published recently in the Journal of the Intensive Care Society) showed a high rate of compliance with a low tidal volume invasive ventilation strategy in patients with severe blunt chest trauma. 5 We sought to determine the rate of adherence to low tidal volume ventilation, and association between tidal volume delivered and patient-relevant outcomes in a cohort of mechanically ventilated patients with chest trauma in a UK tertiary trauma intensive care unit.Following institutional approval, a cohort of 98 consecutive trauma patients with pulmonary contusions (between August 2016 and August 2017) requiring IMV on intensive care unit (ICU) were retrospectively reviewed. The primary end-point was rate of adherence to low tidal volume for the duration of IMV.…”
mentioning
confidence: 99%
“…A recent French observational study (published recently in the Journal of the Intensive Care Society ) showed a high rate of compliance with a low tidal volume invasive ventilation strategy in patients with severe blunt chest trauma. 5 We sought to determine the rate of adherence to low tidal volume ventilation, and association between tidal volume delivered and patient-relevant outcomes in a cohort of mechanically ventilated patients with chest trauma in a UK tertiary trauma intensive care unit.…”
mentioning
confidence: 99%